Asuhan Keperawatan Keluarga Ibu M dengan Pemberian Bawang Hitam pada Penyakit Diabetes Melitus di Wilayah RT 008 RW 003 Kelurahan Bambu Apus Kecamatan Cipayung Jakarta Timur - Rifki Heryandi; Fajar Susanti; Samsuni Samsuni; Thika Marliana (Jurnal Studi Multidisiplin Ilmu, 2023)
Purpose: To find out how to give black garlic to comprehensively lower blood glucose levels in the body to clients or families who have diabetes mellitus problems. Methodology/approach: a type of applied research method or called applied research. Applied research aims to apply, test and evaluate the ability of a theory, which is applied in solving practical problems. The research subject was the application of black garlic therapy to Mrs. M's family. The instrument or measuring tool used in this research was a glucometer to measure blood sugar levels and the SOP for giving black garlic. Results/findings: In this case, the nursing action that can be taken is the administration of black garlic, which from several studies is very effective in reducing blood glucose levels in diabetes mellitus. Limitations: It is hoped that it can become a reference for a more in-depth study of family nursing care for Diabetes Mellitus Contribution: Thank you to the parties who have helped in this research, especially the lecturers and students who have collaborated with village officials